Application of drilling technology in prevention and control of water in coal mine. (June 2020) - Zhao, Shaofei
Abstract: As an important technical means of coal mining, drilling has been widely used in coal mine waterproofing and water control. The complexity of underground coal mines increases the difficulty of drilling. This paper expounds the types of water damage in coal mine and analyzes the technical requirements before, during and after drilling.